Effect of Diets with Varying Levels of Metabolizable Energy on Lactation Performance and Metabolic Profile of Buffaloes - Chaudhari, Alkesh; Tyagi, Nitin; Sediqi, Jawid; Kumar, Sachin; Tyagi, A K (Indian Journal of Animal Nutrition, 2020)
The present study was conducted to ascertain the effect of feeding varying level of metabolisable energy on the production performance and nutrient utilization of Murrah buffaloes. Sixteen advance pregnant Murrah buffaloes (40-50 d before parturition) were divided into three treatment groups on the basis of most probable production ability (MPPA), (2200±241) and lactation number (3.57±0.95). Duration of feeding trial was 130 days i.e. 40 days pre-partum to 90 days post-partum period. Treatment groups were fed 3 different diets as low metabolizable energy (LME), medium metabolizable energy (MME) and high metabolizable energy (HME), at 85%, 100% and 115% of ICAR, 2013 ME requirements respectively. Concentrate mixture, maize green and wheat straw were offered to individual animal as per experiment protocol. As per diet offered, ME intakes was higher in HME followed by MME and LME while metabolizable protein (MP) and crude protein (CP) intakes were similar in all experimental groups. Metabolic trial of 7 days duration was conducted at after 60 days of post-partum feeding and it was observed that apparent digestibility (%) of DM, organic matter (OM) and CP were statistically similar among groups. Neutral detergent fibre (NDF) digestibility was higher in HME group as compared to LME and MME. There was no significant change in blood biochemical profile i.e. NEFA, IGF-1, glucose, BUN, total protein, albumin, globulin, AST and IgG, on feeding different levels of metabolizable energy. The nitrogen balance was not affected by different levels of ME in the diet. HME group had significantly higher milk yield and FPCM (Kg/day). The outcome of the current study indicates that fat and protein corrected milk significantly improved at 115% higher ME with respect to ICAR, 2013 nutrient requirements.